Responsabilidad penal de las personas jurídicas: ¿Resulta el Compliance una medida suficiente y útil para el sistema judicial peruano? - Ugaz Sánchez-Moreno, José (2018)
Compliance is a fairly familiar term among American companies and even in European countries. However, it is a new concept that that is being handled in Peru. The main function of Compliance is to guarantee the integrity of the company and for this it identifies risks and establishes mechanisms that allow them not to become a problem. In response to this, ADVOCATUS had the opportunity to interview four specialists in the field to share their reflections on Compliance in our regulatory framework, as well as in the social context we are in.